History and theory of Scripture translations - Loba-Mkole, Jean-Claude (HTS teologiese studies, 2008)
This article argues for the importance of Bible translations through its historical achievements and theoretical frames of reference. The missionary expansion of Christianity owes its very being to translations. The early Christian communities knew the Bible through the LXX translations while churches today still continue to use various translations. Translations shape Scripture interpretations, especially when a given interpretation depends on a particular translation. A particular interpretation can also influence a given translation. The article shows how translation theories have been developed to clarify and how the transaction source-target is culturally handled. The articles discuss some of these “theoretical frames”, namely the functional equivalence, relevance, literary functional equivalence and intercultural mediation. By means of a historical overview and a reflection on Bible translation theories the article aims to focus on the role of Africa in translation history.